Hero Motivation Model of the Neoromantic Fictional World - Holodiuk, Iryna (Pitannâ lìteraturoznavstva, 2013)
The article analyzes the dominant action modes of neo-romantic character and constructs its motivational model as contrasted to one of romantic character with the methodology of possible worlds theory. The purpose of the paper is to define the specific features of neo-romantic character motivational model through the approach of possible worlds theory (L. Dolezel, M.‑L. Ryan, R. Ronen, T. Pavel). The study analyzes dominant action modes of neo-romantic hero compared to romantic character modes in order to clarify the relation between the Ukrainian romanticism and neo-romanticism which is one of the most polemical problems nowadays. The study determines the correlation of physical or mental acts and evens in the neo-romantic and romantic fictional worlds. The paper analyzes the texts of Lesya Ukrainka, Olga Kobylanska and Panteleymon Kulish. As a result, the study defined neo-romantic hero to be of acratic irrational type with the high degree of mental activity. On the contrary, romantic character is defined to be of impulsive irrational type with the law or even zero degree of autoreflexive activity. The benefits of this study consist in the analysis of Ukrainian literature of early modern period according to the main principle of possible worlds theory. Research implications prove that neo-romantic character interprets his acts, constructs present and future possible worlds, and figures out his/her position toward textual actual reality. Character with such mental activity represents Ukrainian early modern literature.